The effect of a nutrition program for weight loss during the pre-competition period on the body composition, hydration, and mood profile of elite Greco–Roman wrestlers - KÜÇÜK YETGİN, MERAL; AGOPYAN, ANİ (My University, 2023)
Objective: The study aimed to investigate the effect of a nutrition program introduced among elite Greco–Roman wrestlers during the weight-loss period before the competition on the athletes’ body composition, hydration, and mood. Methods: The experimental group comprised the Greco–Roman Wrestling National Team (U23) of different weights (n = 8) and the control group consisted of substitute athletes (n = 8) with the same weights as the experimental group. To achieve the target weight, the experimental group followed a personalized weight loss program under the supervision of a dietitian, whereas the control group lost weight using their own methods. The athletes completed a mood profile questionnaire, food and fluid consumption, urine density evaluation, anthropometric measurements, and body composition assessments were performed. Results: The athletes who followed a balanced diet under the guidance of a dietician had decreased body mass index, body weight, body fat rates (%), and urine density compared to the athletes who used traditional methods (P < 0.05). Negative changes in the control group and positive changes in the experimental group were observed in the mood profile scores (P < 0.05). There was a higher decrease in variables, including energy (kcal), carbohydrate (g/kg), protein (g/kg), fat (g/kg), and micronutrient consumption, in the control group (P < 0.05). Conclusion: Change in nutritional intake at the macro and the micro level was found to be more balanced among male athletes who followed a regular and planned nutrition program under a dietitian’s supervision. In addition, the experimental group had decreased body fat percentages and urine density and underwent a positive change as confirmed by their mood profile.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ORTOPEDİ; Clinical Medicine (MED); CLINICAL MEDICINE; ORTHOPEDICS; Ortopedi ve Spor Hekimliği; Orthopedics and Sports Medicine; Body composition; Hydration; Mood profile; Nutrition; Wrestling